2006
DOI: 10.1017/bjn20061945
|View full text |Cite
|
Sign up to set email alerts
|

Dietary assessment of a population of pregnant women in Sheffield, UK

Abstract: The present study examined the dietary intakes of a population of pregnant women living in the North of England. The objectives of the paper were to assess and describe the dietary intakes of the population and relate the findings to existing data on the diet of pregnant and non-pregnant women in the UK. A total of 250 pregnant women attending their first antenatal appointment at the Jessop Wing Hospital, Sheffield, UK were recruited. Information on their diet was assessed by an interviewer-administered semi-q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

15
34
3

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(52 citation statements)
references
References 20 publications
15
34
3
Order By: Relevance
“…The intakes of most macro-and micronutrients in our study were higher than those reported for pregnant women in England (37,41) , but similar to those found among pregnant women in Finland (39) , the USA (42) and Greece (43) . We attempted to identify groups of women who may be at particular risk of nutrient inadequacy and to whom dietary interventions should be targeted.…”
Section: Main Findingssupporting
confidence: 84%
See 1 more Smart Citation
“…The intakes of most macro-and micronutrients in our study were higher than those reported for pregnant women in England (37,41) , but similar to those found among pregnant women in Finland (39) , the USA (42) and Greece (43) . We attempted to identify groups of women who may be at particular risk of nutrient inadequacy and to whom dietary interventions should be targeted.…”
Section: Main Findingssupporting
confidence: 84%
“…A recent US study (40) reported a much lower inadequacy prevalence (36 % v. 90?8 % in our sample) but, in contrast to Portugal, folate fortification of staple foods is common in the USA. A much lower prevalence was also observed in a large British study but the cut-off points used to define inadequacy of folate intake were very different (37) from those used in the present study. Intake of Fe prior to conception was within recommended levels for most women, but as requirements almost triple during pregnancy with no parallel increase in intake, the prevalence of inadequacy was very high during pregnancy.…”
Section: Main Findingscontrasting
confidence: 66%
“…However that study did not include a control, non-pregnant cohort. Similar findings have been reported in a number of smaller studies in both the UK (6) and the USA (7) . The Norwegian Mother and Child Cohort Study (MoBa) is currently underway with some dietary data published for 40 108 participants (8) .…”
supporting
confidence: 90%
“…The diet quality and variety of the young Australian cohort that we have studied appears to be suboptimal, as evident by the discrepancies between the recommended and reported intake levels, especially for folate, fibre and Fe. These key nutrients have also been found to be at suboptimal levels of intake in pregnant women in the UK and Norway, and in pregnant and non-pregnant controls in the USA (5)(6)(7) . The ARFS was previously developed to evaluate the diet quality of mid-aged Australian women and it has performed well in analyses of nutritional and some morbidity-related indices (24,25) .…”
Section: Discussionmentioning
confidence: 99%
“…This presents a challenging issue for public health authorities and for pregnant women, as the risk of listeriosis v. inadequate nutrient intakes needs to weighed up (14) . Some studies have examined the diet quality of pregnant women in relation to nutrient intakes (15)(16)(17)(18)(19) . Hure et al found that women of childbearing age in Australia are not meeting key nutrient intakes and concluded that those who were trying to become pregnant or were pregnant did not appear to consume a variety of nutritious foods (15) .…”
mentioning
confidence: 99%